To Plant or Not to Plant: When can Planting Facilitate Mangrove Restoration? - van Bijsterveldt, Celine E. J.; Debrot, Adolphe O.; Bouma, Tjeerd J.; Maulana, Moch B.; Pribadi, Rudhi; Schop, Jessica; Tonneijck, Femke H.; van Wesenbeeck, Bregje K. (Frontiers in Environmental Science, 2022)
Global change processes such as sea level rise and the increasing frequency of severe storms threaten many coastlines around the world, and trigger the need for interventions to make these often densely-populated areas safer. Mangroves could be implemented in Nature-Based Flood Defense, provided that we know how to conserve and restore these ecosystems at those locations where they are most needed. In this study, we investigate how best to restore mangroves along an aquaculture coast that is subject to land-subsidence, comparing two common mangrove restoration methods: (1) mangrove restoration by planting and (2) Ecological Mangrove Restoration (EMR), the assistance of natural mangrove regeneration through mangrove habitat restoration. Satellite data revealed that historically, landward mangrove expansion into the active pond zone has mainly occurred through mangrove planting on pond bunds. However, there is potential for EMR measures, as propagule trap data from the field revealed that propagules of pioneer species were up to 21 times more abundant in creeks of the pond zone than near their source in the coastal zone. This was especially true during the prevailing onshore winds of the wet-season, suggesting that smart seasonal sluice gate management could help to efficiently trap seeds in target ponds. In the coastal zone, field experiments showed that permeable brushwood dams, aimed at expanding mangrove habitat, could not sufficiently overcome subsidence rates to increase natural mangrove expansion, but did significantly increase the survival of already established (planted) seedlings compared to wave-exposed sites. The survival and growth rate of EMR-supported plantings varied between species. Out of the 4 planted species, Rhizophora mucronata had the highest survival (67%) but the lowest growth rate. Whereas the pioneer species Avicennia alba and Avicennia marina had lower survival rates (resp. 35 and 21%), but significantly higher growth rates, even resulting in fruiting young trees within a 16-month timeframe. Overall, we conclude that i) EMR has potential in the pond zone, given that propagules were observed to reach well into the backwaters; and ii) that mangrove recovery in the coastal zone may be facilitated even at very challenging coastal sites by combining EMR with planting of pioneer species.